The Effects Of Vertıcal Headgear Therapy On The Morphology Of Cranıofacıal Structures - Haluk İşeri; Erhan Özdiler (Galenos Yayinevi, 1992)
Bones of the craniofacial complex have been subjected to functional and orthopaedic forces during growth in order to redirect the skeletal growth. In the present study it is aimed to analyze the effects of vertical maxillary force application on the craniofacial skeleton. The study was performed on 9 subjects who had undergone vertical headgear therapy and, 9 control subjects who had received no orthodontic treatment. Gonial angle and the height of middle cranial fossa (s-ar) was significantly increased in the treatment group in comparison to the control group during the observation period.